POETICAL REALISM OF JEFTIMIJE JEFTA VANČETOVIĆ – ORIGIN AND CHARACTERISTICS (Heritage, 2025)
This paper examines the poetics of the Serbian academic painter Jeftimije Jefta Vančetović (1907–1992), born in Priština. Combining the stylistic patterns of realism and en plein air, which he adopted from Ljubomir Ivanović (1882–1945) and Beta Vukanović (1872–1972) during his studies at the School of Fine Art in Belgrade between 1926 and 1930, Vančetović achieved their specific symbiosis, expressing himself primarily in the technique of watercolors (aquarelle). Thematically tied to the disappearing scenes of traditional architecture and authentic urban ambient ensembles of Balkan cities (primarily from his native Kosovo and Metohija, Macedonia and Central Serbia), this artist based his artistic expression on a chronicler’s recording of a world that was disappearing in the 20th century before the general modernization and urbanization. However, in the poetics of Jeftimije Jefta Vančetović, there is a noticeable shift away from factual realism, towards the en plein air (or impressionistic) visual language, which in the artist's work reaches its peak in the period between the two world wars. The paper aims to place the ouvre of this unjustly forgotten artist into the space of scientific discourse, to establish a framework for interpreting his style and to initiate the possibility of further research.
Keywords: Jeftimije Jefta Vančetović, realism, en plein air, aquarelle, Serbian painting.